On a New Subclass of Multivalent Functions Defined by Hadamard Product - Atshan, Waggas Galib; Battor, Ali Hussein; Kadhim, Azhar Jawad (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we introduce and study the class of multivalent functions in the open unit disk U= {Z c1|z|<1} which are defined by the convolution (or Hadamard product). Then we give the coefficient inequality, closure theorems, neighborhoods of theclass ,partial sums, weighted mean theorem, convolution, distortion and growth bounds.